2D Transition Metal Dichalcogenide Heterostructures for p‐ and n‐Type Photovoltaic Self‐Powered Gas Sensor. (9th September 2020) - Kim, Youngjun; Lee, Sangyoon; Song, Jeong‐Gyu; Ko, Kyung Yong; Woo, Whang Je; Lee, Suk Woo; Park, Minwoo; Lee, Hoonkyung; Lee, Zonghoon; Choi, Hyunyong; Kim, Woo‐Hee; Park, Jusang; et al.
Abstract: 2D transition metal dichalcogenides (TMDs) have attracted much attention for their gas sensing applications due to their superior responsivity at typical room temperature. However, low power consumption and reliable selectivity are the two main requirements for gas sensors to be applicable in future electronic devices. Herein, a p‐type (WSe2 /WS2 ) and n‐type (MoS2 /WSe2 ) photovoltaic self‐powered gas sensor is demonstrated using 2D TMD heterostructures for the first time. The gas sensors are operated by the photovoltaic effect of 2D TMD heterostructures, which are uniformly synthesized by the vacuum‐based synthesis. The gas sensing properties of the WSe2 /WS2 and MoS2 /WSe2 heterostructure gas sensors are investigated for NO2 and NH3 with changing gas concentration, and each sensor exhibits selectivity to NO2 and NH3 . From the results, it is confirmed that the 2D TMD heterostructures can be a viable platform for highly sensitive, selective gas sensor applications without external bias due to their photovoltaic features. Further, this study contributes toward revealing the gas sensor mechanism in 2D TMD heterostructure. Abstract : A photovoltaic self‐powered gas sensor is demonstrated using a 2D transition metal dichalcogenide (TMD) heterostructure. Depending on the surface layer, p‐ and n‐type gas sensors are fabricated with selectivity to NO2 and NH3 gas. In addition, this study contributes toward revealing the sensing mechanism in 2D TMD heterostructures.